Potencial Medicinal das Acanthaceae do Cerrado - Vargem, Daiana da Silva; Braz, Vivian da Silva; Peixoto, Josana de Castro; Lemes, Erick de Oliveira (Fronteira: Journal of Social, Technological and Environmental Science, 2023)
The cerrado has unique fauna and flora characteristics, which endemic species, and represents one-third of the species of living beings that are constituents of Brazilian biodiversity. The Family Acanthaceae distributed in tropical and subtropical regions around the world. Thus, the aim of this study was performing a literature review and data analysis regarding the medicinal potential of cerrado acanthaceae. The methodology used this study was the literature review and data analysis, which proved to be more appropriate for this type of research, because it aims to identify the quantitative and qualitative production of the theme in question in recent years. Among the studies conducted on the distinct species of medicinal plants of the Cerrado, the species of the family Acanthaceae stand out, which has in Brazil one of the main centers of its biodiversity.